Fiber-optic Sensing for Press Forming of L-shaped Thermoplastic Composites. (2017) - Takeda, Shin-ichi; Tsukada, Takuhei; Minakuchi, Shu; Takeda, Nobuo; Iwahori, Yutaka
Abstract: Fiber Bragg grating sensors (FBG) were embedded into the CF/PPS laminates to demonstrate the monitoring of the press forming of the L-shaped CFRTPs (Carbon Fiber Reinforced Thermoplastics). In-plane strain of the flexion represented a unique change from contact with the flat plate to position of bottom dead center. Residual strains along the FBG are able to evaluate directly, which is mainly caused by cooling part of the press forming process. Moreover a non-axisymmetric strain in the FBG was evaluated at the flexion. Fiber-optic sensing probably become beneficent technology to improve a press forming process of CFRTPs.